OP16 Assessing The Viability Of Medical Equipment Procurement In Hospital. (2019) - Avdeyev, Andrey; Benberin, Valeriy; Shanazarov, Nasrulla; Kudaibergenova, Maigul; Kaptagayeva, Aigul; Hailey, David; Zhumagali, Yenglik; Magzumova, Raushan; Makalkina, Larissa
Abstract : Introduction: ABC-VEN analysis is an easy method of clinical and economic analysis on the costs of drug coverage and an important tool for monitoring and ensuring the rational use of medicines. However, this methodology is difficult to apply in assessing the viability of medical equipment procurement (MEP) in hospital. Using a combined model of ABC analysis and Multiple criteria decision analysis (MCDA) may be more appropriate to apply to MEP. Methods: We created five standardized criteria, which present the main results of assessment of the viability of MEP for implementing new health technologies (HTs). These criteria address the following: 1) Novelty/innovation; 2) Comparative clinical effectiveness and safety; 3) Relevance (demand); 4) Economic effectiveness; and 5) Payback period. Based on these criteria we determine the threshold values of priority for MEP: 1) High priority; 2) Medium priority; 3) Low priority. Results: Using the ABC model and five standardized criteria, we analyzed all proposals from the Hospital units for implementing new HTs connected with MEP for 2018. In total, proposals contained 11 items of ME, among them three items were in group A (27%), two items were in group B (18%), and six items were in group C (55%). All items were high priority for procurement with the exception of one item from group B with medium priority. Items with low priority were not revealed which can be considered as a direct indicator of the operational effectiveness of Hospital-based HTA Unit. Excluding ME with a medium priority from the procurement plan would reduce Hospital costs by 13.5 percent. Conclusions: Combined ABC and MCDA analysis in the process of assessment the viability of MEP can give the opportunity to make comparative assessment of different types of ME based on standardized criteria; determine the priority for procurement of new ME; and avoid the influence of subjective factors of the managerial decision-making process in hospital.